Obtaining the CAD Flow Models in the Francis Turbine of the Sancancio Hydroelectric Power Plant by Means of Reverse Engineering - Sierra, Jorge; Correa, Edwin (International Journal of Integrated Engineering, 2020)
This article presents the process for obtaining the CAD flow models in a Francis turbine. The analysis stage in this turbine includes the use of the latest generation optical equipment to obtain the surfaces of each of the component elements of the Francis turbine. After obtaining 3D scans, is used special software for CAD modelling and reverse engineering to extract the complex NURBS surfaces of several of the main components of the turbine and finally the flow volumes which are of vital importance in the previous studies of the research called CFD computational analysis of the influence on the opening of the blades in a Francis turbine on the side of the suction ring in the small hydroelectric power station of Sancancio belonging to the CHEC S.A E.S. P EPM Group